2022
DOI: 10.1089/tmj.2020.0561
|View full text |Cite
|
Sign up to set email alerts
|

Telemedicine Utilization at an Academic Medical Center During COVID-19 Pandemic: Are Some Patients Being Left Behind?

Abstract: Introduction:The purpose of this study was to examine the use of telemedicine at one academic health care center during the COVID-19 pandemic to identify opportunities to improve access to this novel delivery method of care. Methods: All patients who underwent telemedicine visits at one urban academic medical center between March 2020 and June 2020 were included. All departments were included including surgical and nonsurgical. Demographic data, primary language, and visit type were collected. Primary zip code… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 11 publications
2
11
0
Order By: Relevance
“…Young adults, females, single adults, those with a higher level of education, the employed, and those with lower income were more likely to use virtual clinics. Those factors were in accordance with previous literature that shows an association between using virtual care and sociodemographic characteristics such as age [ 23 , 24 ], gender [ 23 , 24 ], marital status [ 23 ], income [ 23 , 25 , 34 ], and education level [ 25 ].…”
Section: Discussionsupporting
confidence: 91%
“…Young adults, females, single adults, those with a higher level of education, the employed, and those with lower income were more likely to use virtual clinics. Those factors were in accordance with previous literature that shows an association between using virtual care and sociodemographic characteristics such as age [ 23 , 24 ], gender [ 23 , 24 ], marital status [ 23 ], income [ 23 , 25 , 34 ], and education level [ 25 ].…”
Section: Discussionsupporting
confidence: 91%
“…These results are consistent with the early pandemic reports from March through May 2020, in New York, San Francisco, and Philadelphia. [6][7][8]10 We now see that these disparities have persisted in June through September, beyond the instability of the initial telehealth expansion and are reproduced across different urban centers. The consistency of these disparities across multiple institutions suggests the contribution of larger structural inequities.…”
Section: Discussionmentioning
confidence: 86%
“…The main barrier identified was reliable internet connectivity. Multiple other studies have found consistent barriers to telemedicine care included non-English language, public insurance, older age, and minority race/ethnicity [16 ▪ ,28 ▪ –31 ▪ ].…”
Section: Barriers To Telemedicine Usementioning
confidence: 85%